Composite ultraviolet-resistant additive, ultraviolet-resistant high polymer material coating and preparation method thereof

CN122941229APending Publication Date: 2026-10-20SHENYANG GOLDEN FALCON TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611428403.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]针对现有技术中抗紫外高分子材料涂层存在添加剂与基材相容性差、分散不均、结合力弱,且制备工艺成本高、涂层性能不稳定的不足,本发明提供了一种复合抗紫外添加剂及抗紫外高分子材料涂层和制法,该方法以“复合抗紫外添加剂精准制备-高效分散固化”为核心,通过制备“无机抗紫外核-有机抗紫外外壳”复合抗紫外添加剂改性聚氨酯或环氧树脂,制得抗紫外高分子材料涂层

Benefits of technology

1、该方法通过制备“无机抗紫外核-有机抗紫外外壳”复合抗紫外添加剂,有效解决了现有技术中抗紫外添加剂与高分子基材相容性差、分散不均的问题,复合抗紫外添加剂在高分子材料涂层体系中能均匀分散,与聚氨酯或环氧树脂基材结合紧密,显著提升了涂层的抗紫外持久性,同时保证了涂层的附着力等关键性能,且制备工艺可控性强,有利于降低生产成本,易于实现规模化生产。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention relates to a composite UV-resistant additive, a UV-resistant polymer coating, and its preparation method, belonging to the field of polymer coating technology. The method centers on "precise preparation of the composite UV-resistant additive – efficient dispersion and curing," using a composite UV-resistant additive ("inorganic UV-resistant core – organic UV-resistant shell") to modify polyurethane or epoxy resin to obtain a UV-resistant polymer coating. The prepared composite UV-resistant additive exhibits excellent dispersion in the coating system, superior compatibility with the polyurethane or epoxy resin substrate, and tight bonding, significantly improving the coating's UV resistance durability while ensuring key properties such as adhesion. Furthermore, the preparation process is highly controllable and cost-effective, facilitating production cost reduction and large-scale production. It also meets the weather resistance and UV aging resistance requirements of various applications, including building exteriors and automotive exteriors, providing an efficient and stable new solution for the preparation of UV-resistant polymer coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer coating technology, specifically to a composite UV-resistant additive and a UV-resistant polymer coating and its preparation method. The UV-resistant polymer coating is based on polymer substrates such as polyurethane and epoxy resin, and is a UV-resistant and weather-resistant coating formed by modification with a composite UV-resistant additive. The preparation method balances UV resistance and film-forming stability, and is suitable for outdoor applications such as building exteriors, automotive exteriors, and electronic device housings where high weather resistance and UV aging resistance are required. Background Technology

[0002] Polyurethane, epoxy resin, and other polymer coatings are widely used for outdoor component protection due to their strong adhesion and excellent mechanical properties. However, the ester and ether bonds in the molecular chains of these substrates are easily broken by ultraviolet radiation, leading to aging problems such as loss of gloss, chalking, and cracking. Therefore, UV-resistant additives are needed to modify the coatings and improve their weather resistance. UV-resistant additives, as commonly used modifiers, have the advantages of strong UV absorption and reflection capabilities and good stability, making them ideal UV-resistant modifiers. However, some additives have poor compatibility with polymer substrates, uneven dispersion, and weak bonding with the substrate, making them prone to migration and precipitation during use, leading to a decrease in the coating's UV resistance.

[0003] Currently, existing UV-resistant modification technologies mainly fall into two categories: one is to directly add UV-resistant additives and introduce them into the coating system through physical mixing. While this can improve UV resistance to some extent, it cannot solve the problem of uneven additive dispersion. The other is to modify the surface of the additives, using modifiers to improve their compatibility with the substrate, enhance dispersion, and improve UV resistance durability. However, modifiers are expensive, and the modification process is complex, making it difficult to balance modification effectiveness with production costs. In addition, existing UV-resistant polymer coating preparation processes (such as spraying and brushing) suffer from uneven coating thickness and poor UV resistance stability, making it difficult to meet the long-term protection requirements of high-end outdoor components.

[0004] In summary, existing technologies cannot simultaneously achieve the synergistic effect of "strong bonding between additives and substrates", "stable UV resistance of coatings", and "low-cost preparation". There is an urgent need to develop an integrated technical solution that combines additive modification, performance stability and low-cost preparation. Summary of the Invention

[0005] To address the shortcomings of existing UV-resistant polymer coatings, such as poor compatibility between additives and substrates, uneven dispersion, weak adhesion, high preparation costs, and unstable coating performance, this invention provides a composite UV-resistant additive, a UV-resistant polymer coating, and a preparation method. This method centers on "precise preparation of the composite UV-resistant additive – efficient dispersion and curing." It involves preparing a composite UV-resistant additive modified with polyurethane or epoxy resin, consisting of an "inorganic UV-resistant core and an organic UV-resistant shell," to obtain the UV-resistant polymer coating. First, a composite UV-resistant additive is prepared, with a nano-metal oxide core, preferably ZnO, a benzotriazole-based organic UV-resistant agent as the coating layer, and a silane coupling agent as the modification layer. Then, polyurethane or epoxy resin is mixed with a dispersant and a leveling agent, followed by the addition of the composite UV-resistant additive and high-speed dispersion to form a uniform slurry. Finally, a suitable curing agent is added, the substrate is coated, and the mixture is cured to obtain the UV-resistant polymer coating. By precisely controlling the temperature, rotation speed, time, and material ratio of each step, we ensure that the composite UV-resistant additives are evenly dispersed and the UV-resistant polymer coating has stable performance.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The present invention discloses a composite UV-resistant additive with a nano-metal oxide core, a coating layer around the core, and a modification layer around the coating layer. The modification layer consists of a silane coupling agent and the coating layer consists of a benzotriazole organic UV-resistant agent.

[0007] By mass ratio, nano-metal oxides: silane coupling agents: benzotriazole organic UV stabilizers = 40-50%: 5-10%: 40-50%.

[0008] The nano-metal oxide is preferably one of ZnO, FeO, Fe2O3, NiO, TiO2, Al2O3, ZrO2, CuO, MgO, CeO2, Fe3O4, SnO2, and WO3, with an average particle size of 20-30 mm.

[0009] The composite UV-resistant additive has an average particle size of 50~200nm, and its dispersibility is such that there is no obvious agglomeration in the polymer matrix and organic solvent, the particle size distribution is uniform, and the compatibility with the polymer matrix is ​​excellent after hydrophilic and oleophobic modification.

[0010] The method for preparing the composite UV-resistant additive includes dispersing nano-metal oxides in a solvent, modifying them by adding a silane coupling agent to obtain modified nano-metal oxides; mixing the modified nano-metal oxides with a benzotriazole UV-resistant agent, stirring and reacting, and drying to obtain the composite UV-resistant additive.

[0011] Specifically, the following steps are included: Step 1: Disperse the nano-metal oxide in an alcohol solvent, then add a silane coupling agent and ultrasonically modify it for 1-2 hours to ensure that the silane coupling agent is uniformly coated on the surface of the nano-metal oxide, preferably for 1.5 hours, to obtain the modified nano-metal oxide; Step 2: Mix the modified nano-metal oxide and benzotriazole UV stabilizer, stir and react at 60-80℃ for 3-4 hours, preferably at 70℃ for 3.5 hours, and then centrifuge and dry to obtain the composite UV stabilizer additive.

[0012] In step 1, the solid-liquid ratio is 1 g:(15-25) mL for nano-metal oxide and 1 g:20 mL for alcohol solvent, to ensure that the nano-metal oxide is fully dispersed and avoids agglomeration.

[0013] In step 1, the amount of silane coupling agent added is 5-15% of the mass of the nano-metal oxide, which matches the mass ratio of silane coupling agent in the composite UV-resistant additive, ensuring the modification effect.

[0014] In step 2, the amount of benzotriazole UV stabilizer added is 80-125% of the mass of the modified nano-metal oxide, corresponding to a mass ratio of 40-50% in the composite UV stabilizer additive, to achieve uniform coating.

[0015] In step 2, the drying temperature is preferably 80-100℃ and the drying time is 2-3 hours to ensure that the material is fully dried and to avoid residual solvent affecting product performance.

[0016] In step 2, after centrifugation and drying, the particle size distribution of the composite UV-resistant additive needs to be tested to ensure good dispersibility.

[0017] The UV-resistant polymer coating of the present invention uses polyurethane or epoxy resin as the polymer matrix and adds the above-mentioned composite UV-resistant additives.

[0018] The aforementioned UV-resistant polymer coating has an adhesion grade of 1-2 (GB / T 9286-1998 standard); the UV-resistant agent migration rate is ≤0.5% / 24h, effectively ensuring the long-term stability of the coating's UV resistance.

[0019] The aforementioned UV-resistant polymer coating contains the following components and their mass fractions: 60-80 parts of polymer matrix, 2-3 parts of dispersant, 1-2 parts of leveling agent, 10-15 parts of composite UV-resistant additive, and 5-8 parts of curing agent.

[0020] The method for preparing the aforementioned UV-resistant polymer coating includes the following steps: S1: According to the formula, stir the polymer matrix, dispersant and leveling agent evenly to obtain the initial polymer system; S2: Add the composite UV-resistant additive to the polymer initial system, heat to 50-60℃, and disperse at high speed at 1200-1500 rpm for 1-1.5 hours to form a uniform slurry; S3: Add the curing agent to the uniform slurry, stir evenly, and cure to obtain an anti-UV polymer material coating.

[0021] In S1, the polymer matrix is ​​selected from polyurethane resin or epoxy resin.

[0022] In S1, the dispersant is selected from polycarboxylate dispersants, preferably those with high dispersion efficiency; the leveling agent is selected from those that can effectively improve the surface smoothness of the coating.

[0023] In S1, the stirring speed for uniform mixing is 800-1000 rpm, preferably 900 rpm, and the stirring time is 20-40 min.

[0024] In step S2, the addition rate of the composite UV-resistant additive is 0.5 to 1.0 parts / min (by mass), preferably with the temperature controlled at 55°C, the rotation speed at 1300 rpm, and the duration at 1.2 h, to ensure that the composite UV-resistant additive is uniformly dispersed in the system and to avoid agglomeration.

[0025] In step S3, the type of curing agent is selected based on the polymer matrix, such as isocyanates suitable for polyurethane. The amount of curing agent is strictly added according to the formula ratio, the coating thickness is kept uniform, and room temperature curing requires a well-ventilated and dry environment. During drying curing, the temperature is gradually increased to avoid bubbles. After curing, the coating adhesion and UV resistance are tested. The substrate surface needs to be pretreated to remove oil and impurities. The curing agent suitable for polyurethane is an isocyanate, and the substrate includes metals and plastics.

[0026] In S3, curing can be performed at room temperature or at high temperature. The high-temperature curing temperature is 80-100℃ and the curing time is 24-48h.

[0027] The UV-resistant polymer coating of the present invention retains a gloss rate of 84-90% after aging under a xenon lamp for 1000 hours; and after immersing the UV-resistant polymer coating in ethanol at 50°C for 24 hours, the UV-resistant agent migration rate reaches 0.21-0.45%, the UV-resistant polymer coating shows no obvious discoloration, the coating is transparent, and the haze is 2.1-3.0%.

[0028] The present invention provides a composite UV-resistant additive, a UV-resistant polymer coating, and a preparation method thereof, the advantages of which are as follows: 1. This method effectively solves the problems of poor compatibility and uneven dispersion of anti-UV additives with polymer substrates in the prior art by preparing an "inorganic anti-UV core-organic anti-UV shell" composite anti-UV additive. The composite anti-UV additive can be uniformly dispersed in the polymer coating system and tightly bonded to the polyurethane or epoxy resin substrate, which significantly improves the anti-UV durability of the coating. At the same time, it ensures the key properties of the coating such as adhesion. Moreover, the preparation process is highly controllable, which is conducive to reducing production costs and is easy to achieve large-scale production.

[0029] 2. This method focuses on "precise preparation of composite UV-resistant additives - efficient dispersion and curing". It prepares a composite UV-resistant additive of "inorganic UV-resistant core - organic UV-resistant shell" to modify polyurethane or epoxy resin, thereby obtaining a UV-resistant coating. By precisely controlling the process parameters of each step, such as ultrasonic modification time, stirring reaction temperature, high-speed dispersion speed and temperature, the stability of the composite UV-resistant additive and the reliability of the coating performance are ensured. The obtained coating can adhere well to the surface of different substrates (such as metal and plastic), has a wide range of applications, and can meet the UV resistance requirements in various scenarios. It provides an efficient and stable new solution for the preparation of UV-resistant polymer coatings.

[0030] 3. The composite UV-resistant additive prepared by this invention can be well dispersed in the coating system and has excellent compatibility with the substrate, effectively solving the problem of uneven dispersion of traditional UV-resistant additives. Compared with the traditional process of directly adding UV-resistant additives, the UV-resistant polymer coating prepared by this method has significantly improved UV resistance durability, while ensuring the adhesion and other properties of the coating. Moreover, the preparation process is highly controllable, which helps to reduce process costs.

[0031] 4. The composite UV-resistant additive of the present invention forms a three-layer structure through structural configuration, wherein the silane coupling agent first reacts with the hydroxyl groups on the surface of the metal oxide core and covalently binds to the particle surface, with its organic ends exposed outward; the benzotriazole then reacts and connects with these outward organic ends; the hydrophobic alkyl chain of the silane coupling agent has the least polarity and will spontaneously extend to the outermost layer of the entire particle, thereby forming a structure with nano-metal oxide as the core, the outer periphery of the core as the coating layer, and the outer periphery of the coating layer as the modification layer. Detailed Implementation

[0032] This invention provides a polyurethane or epoxy resin coating modified with a composite UV-resistant additive based on an "inorganic UV-resistant core and an organic UV-resistant shell", which can achieve a synergistic improvement in the coating's "strong UV resistance, high stability and excellent adhesion".

[0033] The following detailed description, in conjunction with embodiments, illustrates the composite UV-resistant additives and composite UV-resistant polymer coatings and their preparation methods provided by the present invention. However, these descriptions should not be construed as limiting the scope of protection of the present invention.

[0034] Example 1:

[0035] A method for preparing an anti-ultraviolet polymer coating includes the following steps: Step 1: 4g of nano-metal oxide (ZnO with a particle size of 20-30nm was used in this example) was dispersed in 100mL of ethanol, and 0.5g of silane coupling agent (KH-550) was added. The mixture was ultrasonically treated for 1.5h. Then, 4g of benzotriazole UV stabilizer (UV-327) was added, and the mixture was stirred and reacted at 70℃ for 3.5h. After the reaction was completed, the mixture was centrifuged and dried to obtain 8.2g of composite UV stabilizer additive.

[0036] Step 2: Add 70g of polyurethane resin (50% solid content), 2.5g of polycarboxylate dispersant, and 1.5g of leveling agent to a mixing tank and stir at 900rpm for 30min to ensure thorough mixing of all components.

[0037] Step 3: Add 12g of the composite UV-resistant additive prepared in step 1 to the above mixture, heat to 55℃, and disperse at 1300rpm for 1.2h to form a uniform slurry.

[0038] Step 4: Add 6g of isocyanate curing agent to the uniform slurry, stir evenly, and then coat it onto the surface of the aluminum alloy substrate. Cur it at room temperature for 48 hours to finally form a UV-resistant polymer material coating with a thickness of 50μm.

[0039] Tests showed that the coating prepared in this embodiment retained 88% of its gloss after 1000 hours of xenon lamp aging; and after immersing the coating in ethanol at 50°C for 24 hours, the UV stabilizer migration rate reached 0.3%, the coating showed no obvious discoloration, was transparent, had a haze of 2.1%, and exhibited significant UV stability and compatibility with polyurethane resin.

[0040] Example 2:

[0041] A method for preparing an anti-ultraviolet polymer coating includes the following steps: Step 1: 5g of nano-metal oxide (FeO in this example, with a particle size of 20-30nm) was dispersed in 120mL of ethanol, and 0.6g of silane coupling agent (KH-560) was added. The mixture was ultrasonically treated for 1.5h. Subsequently, 4.5g of benzotriazole UV stabilizer (UV-326) was added, and the mixture was stirred and reacted at 70℃ for 3.5h. After the reaction was completed, the mixture was centrifuged and dried to obtain 9.3g of composite UV stabilizer additive.

[0042] Step 2: Add 65g of epoxy resin (E-44), 2g of polycarboxylate dispersant, and 1g of leveling agent to a mixing tank and stir at 900 rpm for 30 minutes to ensure thorough mixing of all components.

[0043] Step 3: Add 10g of the composite UV-resistant additive obtained in step 1 to the above mixture, heat to 55℃, and disperse at 1300rpm for 1.2h to form a uniform slurry.

[0044] Step 4: Add 5g of amine curing agent to the uniform slurry, stir evenly, and then coat it onto the surface of the plastic substrate. Dry and cure at 80℃ for 24h to finally form a UV-resistant polymer material coating with a thickness of 45μm.

[0045] Tests showed that the coating prepared in this embodiment retained 85% of its gloss after 1000 hours of xenon lamp aging; and after immersing the coating in ethanol at 50°C for 24 hours, the UV stabilizer migration rate reached 0.21%, the coating showed no obvious discoloration, was transparent, had a haze of 2.8%, and exhibited significant UV stability and compatibility with polyurethane resin.

[0046] Example 3:

[0047] A method for preparing an anti-ultraviolet polymer coating includes the following steps: Step 1: 4.5g of nano-metal oxide (NiO in this example, with a particle size of 20-30nm) was dispersed in 110mL of ethanol, and 0.55g of silane coupling agent (KH-550) was added. The mixture was ultrasonically treated for 1.5h. Subsequently, 4.5g of benzotriazole UV stabilizer (UV-327) was added, and the mixture was stirred and reacted at 70℃ for 3.5h. After the reaction was completed, the mixture was centrifuged and dried to obtain 8.8g of composite UV stabilizer additive.

[0048] Step 2: Add 60g of polyurethane resin (50% solid content), 3g of polycarboxylate dispersant, and 2g of leveling agent to a mixing tank and stir at 900rpm for 30min to ensure thorough mixing of all components.

[0049] Step 3: Add 15g of the composite UV-resistant additive obtained in step 1 to the above mixture, heat to 55℃, and disperse at 1300rpm for 1.2h to form a uniform slurry.

[0050] Step 4: Add 8g of isocyanate curing agent to the uniform slurry, stir evenly, and then coat it onto the surface of the aluminum alloy substrate. Curing is carried out at room temperature for 48 hours to finally form a UV-resistant polymer material coating with a thickness of 55μm.

[0051] Tests showed that the coating prepared in this embodiment retained 84% of its gloss after 1000 hours of xenon lamp aging; and after immersing the coating in ethanol at 50°C for 24 hours, the UV stabilizer migration rate reached 0.45%, the coating showed no obvious discoloration, was transparent, had a haze of 3.0%, and exhibited significant UV stability and compatibility with polyurethane resin.

[0052] Example 4:

[0053] A method for preparing an anti-ultraviolet polymer coating includes the following steps: Step 1: 4.5g of nano-metal oxide (CuO in this example, with a particle size of 20-30nm) was dispersed in 110mL of ethanol, and 0.55g of silane coupling agent (KH-550) was added. The mixture was ultrasonically treated for 1.5h. Subsequently, 4.5g of benzotriazole UV stabilizer (UV-327) was added, and the mixture was stirred and reacted at 70℃ for 3.5h. After the reaction was completed, the mixture was centrifuged and dried to obtain 8.2g of composite UV stabilizer additive.

[0054] Step 2: Add 60g of epoxy resin (30% solid content), 3g of polycarboxylate dispersant, and 2g of leveling agent to a mixing tank and stir at 900rpm for 30min to ensure thorough mixing of all components.

[0055] Step 3: Add 15g of the composite UV-resistant additive obtained in step 1 to the above mixture, heat to 55℃, and disperse at 1300rpm for 1.2h to form a uniform slurry.

[0056] Step 4: Add 8g of isocyanate curing agent to the uniform slurry, stir evenly, and then coat it onto the surface of the aluminum alloy substrate. Curing is carried out at room temperature for 48 hours to finally form a UV-resistant polymer coating with a thickness of 53μm.

[0057] Example 4:

[0058] A method for preparing an anti-ultraviolet polymer coating includes the following steps: Step 1: 4.5g of nano-metal oxide (MgO in this example, with a particle size of 20-30nm) was dispersed in 110mL of ethanol, and 0.55g of silane coupling agent (KH-550) was added. The mixture was ultrasonically treated for 1.5h. Subsequently, 4.5g of benzotriazole UV stabilizer (UV-327) was added, and the mixture was stirred and reacted at 60℃ for 4h. After the reaction was completed, the mixture was centrifuged and dried to obtain 8.6g of composite UV stabilizer additive.

[0059] Step 2: Add 60g of epoxy resin (30% solid content), 2g of polycarboxylate dispersant, and 1g of leveling agent to a mixing tank and stir at 800rpm for 40min to ensure thorough mixing of all components.

[0060] Step 3: Add 10g of the composite UV-resistant additive obtained in step 1 to the above mixture, heat to 50℃, and disperse at 1200rpm for 1h to form a uniform slurry.

[0061] Step 4: Add 5g of isocyanate curing agent to the uniform slurry, stir evenly, and then coat it onto the surface of the aluminum alloy substrate. Curing is carried out at room temperature for 48 hours to finally form a UV-resistant polymer material coating with a thickness of 50μm.

[0062] Comparative Example 1: The only difference between Comparative Example 1 and Example 1 is that the "composite anti-UV additive" in step 1 is replaced with 12g of unmodified nano metal oxide ZnO. The other reagent dosages and operating steps are completely consistent with Example 1.

[0063] Tests showed that the coating prepared in this comparative example had a gloss retention rate of only 42% after aging under a xenon lamp for 1000 hours; and due to the agglomeration of nano-metal oxides, the coating transparency decreased significantly, with a haze of ≥30%.

[0064] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that the "composite UV-resistant additive" in step 1 is replaced with 12g of benzotriazole UV-resistant agent (UV-327), while the other reagent dosages and operating steps are completely consistent with Example 1.

[0065] Tests showed that the coating prepared in this comparative example retained 51% of its gloss after 1000 hours of xenon lamp aging; and after immersing the coating in ethanol at 50°C for 24 hours, the UV stabilizer migration rate reached 8.3%, indicating a significant decrease in the coating's UV resistance.

[0066] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that the benzotriazole UV-327 in step 1 is replaced with an equal mass of benzophenone UV-531. The remaining reagent dosages and operating procedures are completely consistent with Example 1.

[0067] Tests showed that the coating prepared in this comparative example had a gloss retention rate of only 45% after aging under a xenon lamp for 1000 hours; and after immersing the coating in ethanol at 50°C for 24 hours, the UV stabilizer migration rate reached 9.5%, the coating yellowed severely, and its UV stability and compatibility with polyurethane resin were significantly worse than those in Example 1.

Claims

1. A composite UV-resistant additive, characterized in that, The core is made of nano-metal oxide, the outer periphery of the core is a coating layer, and the outer periphery of the coating layer is a modification layer. Among them, the silane coupling agent is the modification layer and the benzotriazole organic anti-ultraviolet agent is the coating layer.

2. The composite UV-resistant additive according to claim 1, characterized in that, By mass ratio, the ratio of nano-metal oxide: silane coupling agent: benzotriazole organic UV stabilizer is 40-50%: 5-10%: 40-50%; the average particle size of the composite UV stabilizer is 50-200 nm.

3. The composite UV-resistant additive according to claim 1, characterized in that, The nano-metal oxide is preferably one of ZnO, FeO, Fe2O3, NiO, TiO2, Al2O3, ZrO2, CuO, MgO, CeO2, Fe3O4, SnO2, and WO3, with an average particle size of 20-30 mm.

4. The method for preparing the composite UV-resistant additive according to any one of claims 1-3, characterized in that, Includes the following steps: Nano-metal oxides are dispersed in a solvent and modified with silane coupling agents to obtain modified nano-metal oxides. The modified nano-metal oxides are then mixed with benzotriazole UV inhibitors, stirred, and dried to obtain a composite UV inhibitor.

5. The preparation method of the composite UV-resistant additive according to claim 4, characterized in that, The process involves dispersing nano-metal oxides in a solvent at a solid-liquid ratio of 1 g to (15-25) mL; adding silane coupling agent at 5-15% of the mass of nano-metal oxides and adding benzotriazole UV stabilizer at 80-125% of the mass of modified nano-metal oxides; and stirring at a reaction temperature of 60-80℃ for 3-4 hours.

6. A UV-resistant polymer coating, characterized in that, The polymer matrix is ​​polyurethane or epoxy resin, and the composite UV-resistant additive described in any one of claims 1-3 or the composite UV-resistant additive prepared by the preparation method of claim 4 or 5 is added.

7. The UV-resistant polymer coating according to claim 6, characterized in that, The components and their mass fractions in the UV-resistant polymer coating are as follows: 60-80 parts of polymer matrix, 2-3 parts of dispersant, 1-2 parts of leveling agent, 10-15 parts of composite UV-resistant additive, and 5-8 parts of curing agent.

8. The UV-resistant polymer coating according to claim 6 or 7, characterized in that, The UV-resistant polymer coating retains 84-90% of its gloss after 1000 hours of xenon lamp aging; and after immersing the UV-resistant polymer coating in ethanol at 50°C for 24 hours, the UV-resistant agent migration rate reaches 0.21-0.45%. The UV-resistant polymer coating shows no obvious discoloration, is transparent, and has a haze of 2.1-3.0%.

9. The method for preparing the UV-resistant polymer coating according to any one of claims 6-8, characterized in that, Includes the following steps: S1: According to the formula, stir the polymer matrix, dispersant and leveling agent evenly to obtain the initial polymer system; S2: Add the composite UV-resistant additive to the polymer initial system, heat to 50-60℃, and disperse at high speed at 1200-1500 rpm for 1-1.5 hours to form a uniform slurry; S3: Add the curing agent to the uniform slurry, stir evenly, and cure to obtain an anti-UV polymer material coating.

10. The method for preparing the UV-resistant polymer coating according to claim 9, characterized in that, The polymer matrix is ​​selected from polyurethane resin or epoxy resin; the dispersant is selected from polycarboxylate dispersants; the stirring speed for uniform mixing is 800-1000 rpm, and the stirring time is 20-40 min; the addition rate of the composite UV-resistant additive is 0.5-1.0 parts / min by mass; the type of curing agent is selected according to the polymer matrix, and the curing is selected from room temperature curing or high temperature curing, with a high temperature curing temperature of 80-100℃ and a curing time of 24-48 h.